Efficacy of funcicides in maize growing - Shynkaruk , L. (Quarantine and plant protection, 2022)
Goal. To determine the technical efficiency of fungicidal treatments against helminthosporiosis, rust and fusarium ear rot in the conditions of the western forest-steppe of Ukraine. Methods. Field. The research scheme included 13 variants with different amounts of fungicidal treatments. The following fungicides were used in the experiments: Abacus e.c. (epoxiconazole 62.5 l/ha + pyraclostrobin 62.5 l/ ha), Coronet 300 SC (trifloxystrobin 100 g/l + tebuconazole 200 g /l), Custodia CS (tebuconazole 200 g/l + azoxystrobin 120 g/l), Acanto KS (picoxystrobin — 250 g/l. Records of diseases were performed according to generally accepted methods in the phase of wax ripeness. Results. Studies have shown that fungicidal treatments reduce the development of helminthosporiosis by 14.9—25.9%, rust — by 4.0—19.4% and fusarium ear rot by 3.2—6.3%. The weighted average development of maize diseases depended on the period of application and the amount of fungicidal sprays. Among the one-time treatments, the lowest level of disease development was when spraying in the phase of panicle ejection, among double treatments — 10 leaves and panicle ejection. Three uses of fungicides in the phase of 10 leaves, shedding of panicles and after flowering reduced the development of helminthosporiosis to 4.4%, rust — to 3.5%, fusarium ear rot — to 1.2%. The highest level of protection was obtained in the variant of four preparations in the phase of 10 leaves, ejection of panicles, after flowering and grain filling, where the development of helminthosporiosis was 4.4%, rust — 2.9%, fusarium ear rot — 1.1%. The technical efficiency of the studied drugs increased with increasing number of fungicidal treatments and was the highest in the variant of four applications of fungicides, which is 86.6% against helminthosporiosis, 87.0% against rust and 85.5% against fusarium ear rot. Conclusions. The technical effectiveness of fungicides depends on the period of application of the drug and increases with an increase in the number of treatments. High technical efficiency was noted in the variant of the three-time introduction of fungicides in the phase of 10 leaves, throwing out the panicle and after flowering. The highest efficiency is in the variant of the four-time introduction of fungicides in the phase of 10 leaves, throwing out the panicle, after flowering and filling the grain.